The Students Ability in Translating Newspaper Headlines into English A Case Study - Ismayanti, Devi; Said, Yuyun Ruqiyyat; Usman, Nurhayati; Nur, Muh. Ilham (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study investigates the process of translating newspaper titles from Indonesian to English. This study aims to determine the ability of students to provide equivalent titles of English-language newspapers in Indonesia. In particular, this research is expected to be able to: Overcome the difficulties currently faced by students in translating newspaper titles, showing grammatical deviations that students have in trying to translate newspaper titles, provide evidence of mechanical problems that arise. This research uses a case study approach. There were 15 newspaper headlines which were delivered to as many as 15 respondents who were sixth semester students of the English Department. The data collection method is to talk about instructions to students before starting to translate newspaper titles. The collected data were analyzed using descriptive analysis method. The data obtained is classified into several aspects of analysis including grammatical errors. The results of the analysis show that students earn a percentage depending on their abilities (application of grammar knowledge) or skills, how to translate local newspapers into English, it is true. Therefore, the researcher suggests readers or students to keep themselves busy by reading local newspapers (fajar and kompas) and in English (example: Jakarta post). In this way, they can acquire globalization knowledge and also indirectly improve their vocabulary and grammar.